Discussing the use of behavior analysis laboratories in teaching of psychology (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
This article is an argument about using experimental laboratory as a resource in teaching psychology by the approachs between the use of the laboratory in Teaching Sciences and Behavior Analysis. It is questioned outwhat is the role played by the laboratory and what are its effective contributions as a teaching resource in students’ learning. The functions traditionally associated with the Animal Operant Laboratory are addressed, as well as its main features and his critics. It is emphasized, above all, that the laboratory practices must be as a space for creating conditions in which students can develop skills that will be indispensable in their future profession. It is emphasized, at last, the relevance of conceiving the Behavior Analysis Laboratory not necessarily as Animal Operant Laboratory but as a space conducive to other activities.